2018
DOI: 10.2166/wst.2018.132
|View full text |Cite
|
Sign up to set email alerts
|

Formation of aerobic granular sludge and the influence of the pH on sludge characteristics in a SBR fed with brewery/bottling plant wastewater

Abstract: A laboratory-scale sequencing batch reactor (SBR) was operated for 450 days to assess aerobic granule formation when treating brewery/bottling plant wastewater by consistent application of a feast/famine regime. The experiment was divided into three major periods according to the different operational conditions: (I) no pH control and strong fluctuations in organic loading rate (OLR) (1.18 ± 0.25 kgCOD·(m·day)), (II) pH control and aeration control strategy to reduce OLR fluctuations (1.45 ± 0.65 kgCOD·(m·day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…After seven weeks, the reactors started to accumulate solids on granular surface and in the bulk mixed liquor ( Figure 1A and 1B) which is clearly visible in Figure 2A (i.e., 8 weeks). This was caused by changes in operational parameters (i.e., previously, 7d SRT control with 4 cycles a day 6h long) which however did not affected granular sludge stability, settling characteristics and effluent solids concentrations (Stes et al, 2018).…”
Section: Granular Sludge Morphologymentioning
confidence: 90%
See 2 more Smart Citations
“…After seven weeks, the reactors started to accumulate solids on granular surface and in the bulk mixed liquor ( Figure 1A and 1B) which is clearly visible in Figure 2A (i.e., 8 weeks). This was caused by changes in operational parameters (i.e., previously, 7d SRT control with 4 cycles a day 6h long) which however did not affected granular sludge stability, settling characteristics and effluent solids concentrations (Stes et al, 2018).…”
Section: Granular Sludge Morphologymentioning
confidence: 90%
“…The author indicated an F/M ratio ranging from 0.5-1.4 kg-TCOD kg-TSSm -3 d -1 as optimal in long-term granular stability. Stes et al (2018) found that granular structure treating brewery wastewater is resistant to operational parameters fluctuation at a lower F/M ratio (i.e., 0.01-0.3 kg-TCOD kg-TSS -1 d -1 ) and pH. During one-step AGS brewery wastewater treatment the authors observed long-term granular stability, preserved performance and settling properties.…”
Section: Granular Sludge Morphologymentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, this technology efficiently treats various industrial wastewaters such as textile, dairy, abattoir, livestock, winery, palm oil mill, rubber, petrochemical, and landfill leachate (Caluwé et al 2017;Dobbeleers et al 2017;Nancharaiah & Kiran Kumar Reddy 2018). AGS has shown the most success when treating readily biodegradable industrial wastewater such as malting, brewery, and dairy (Schwarzenbeck et al 2005;Wang et al 2007;Corsino et al 2017;Stes et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…BNR by the use of granular sludge (GS) has been proposed as an energy‐efficient and sustainable technology for the treatment of synthetic, domestic and industrial wastewaters. Stable BNR‐GS processes rely on anaerobic (feast) feeding, to stimulate storage microorganisms, followed by an aerobic famine reaction .…”
Section: Introductionmentioning
confidence: 99%